Work-related and personal factors in shoulder disorders among electronics workers: findings from an electronics enterprise in Taiwan - Po-Ching Chu; Tyng-Guey Wang; Yue Leon Guo (BMC, 2021)
Abstract Background The electronics industry is one of the largest global industries, and significant numbers of workers are engaged in this industry. Evidence suggests two associations, including one between ergonomic risks and shoulder disorders and another between psychological stress and psychological problems among workers in this industry. Investigations on ergonomic risks, psychological stress, and sex effects for shoulder disorders in this industry are limited. This study aimed to explore personal and work-related factors associated with shoulder disorders and to investigate the combined effect of similar ergonomic risk factors. Methods In this cross-sectional study, 931 workers aged 20 to 58 from an electronics factory in Taiwan were recruited. A Nordic musculoskeletal questionnaire was used to assess shoulder symptoms. Sociodemographic factors and work-related factors, including psychological stress, were assessed. One hundred random sample workers with shoulder symptoms underwent a standardized clinical test for the evaluation of subacromial impingement syndrome. The ergonomic risks were assessed by the risk filter of 'upper limb disorders in the workplace', including repetition, posture, force, vibration, and duration of exposure. Results The prevalence of shoulder symptoms was 30.5, and 19% of those with shoulder symptoms had subacromial impingement syndrome. In multivariable analyses, older age (adjusted odds ratio (aOR) = 1.37, 95% CI 1.01-1.86), repetition (aOR = 1.73, 95% CI 1.15-2.60) and posture (aOR = 1.85, 95% CI 1.10-3.11) were associated with shoulder symptoms. Regarding the gender effect, older age (aOR = 1.46, 95% CI 1.01-2.11), repetition (aOR = 1.64, 95% CI 1.00-2.68), posture (aOR = 1.89, 95% CI 1.01-3.52), and force (aOR = 1.68, 95% CI 0.99-2.85) were associated with shoulder symptoms in men, whereas posture (aOR = 2.12, 95% CI 0.99-4.57) was associated with symptoms in women. Conclusions This study implies that repetition and posture are important risk factors for shoulder disorders in the electronics industry. The risk exhibited sex differences, and force was more important for shoulder disorders in men. Such information is useful to help occupational health practitioners and policy makers conduct preventive programmes on shoulder disorders in this working population. Future longitudinal studies on work-related shoulder disorders are warranted.